(untitled) (Research, Society and Development, 2021)
Considered as a set of disorders, temporomandibular disorder (TMD) involves several anatomical structures such as the temporomandibular joint, masticatory muscles and attached structures. Its etiology is multifactorial, and the psychobehavioral factor, especially sleep disorders, is relevant in this context. This study aimed to assess the prevalence of temporomandibular dysfunction (TMD), sleep quality, and possible associations between these variables, in first to fifth year students of the Dental School. A sample of 182 students participated in this study and a questionnaire proposed by the American Academy of Orofacial Pain and the Pittsburgh Sleep Quality Index questionnaire were used to obtain the data. 75.27% of the students were females and 24.72% males. TMD was observed in 45.60% of students, and 68.13% of the students reported poor sleep quality. However, there was no significant association between the variables (TMD and sleep quality, p=0.114). Regarding the severity of TMD, the mild form was more prevalent (34.61%), being more prevalent in females (79.16%). However, there was no significant association between TMD and sleep quality (p=0.317). There was no association between TMD and sleep quality in the studied population.